2019
DOI: 10.3390/v11070597
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus-B4 Infection of Human Primary Pancreatic Ductal Cell Cultures Results in Impairment of Differentiation into Insulin-Producing Cells

Abstract: Coxsackievirus-B4 (CV-B4) E2 can persist in the pancreatic ductal-like cells (Panc-1 cell line), which results in an impaired differentiation of these cells into islet-like cell aggregates (ICA). In this study, primary pancreatic ductal cells obtained as a by-product of islet isolation from the pancreas of seven brain-dead adults were inoculated with CV-B4 E2, followed-up for 29 days, and the impact was investigated. Viral titers in culture supernatants were analyzed throughout the culture. Intracellular viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Human pancreatic cells were harvested from brain-dead adults in agreement with the French law and ethical committee of our institution. The exocrine fraction was extracted and processed as described previously [29][30][31]. Briefly, pancreatic cells were seeded in six-well plates in Dulbecco's Modified Eagle Medium (DMEM) containing 3 g/L glucose, 10% fetal bovine serum (FBS) (Gibco, Thermofisher Scientific, Courtaboeuf, France), 1% insulin transferrin selenium (Sigma-Aldrich, Saint-Quentin-Fallavier, France), and 1% penicillin/streptomycin (Gibco), as well as 50 µg/mL Geneticin (G418, Sigma-Aldrich) to limit fibroblast overgrowth.…”
Section: Human Pancreatic Cellsmentioning
confidence: 99%
“…Human pancreatic cells were harvested from brain-dead adults in agreement with the French law and ethical committee of our institution. The exocrine fraction was extracted and processed as described previously [29][30][31]. Briefly, pancreatic cells were seeded in six-well plates in Dulbecco's Modified Eagle Medium (DMEM) containing 3 g/L glucose, 10% fetal bovine serum (FBS) (Gibco, Thermofisher Scientific, Courtaboeuf, France), 1% insulin transferrin selenium (Sigma-Aldrich, Saint-Quentin-Fallavier, France), and 1% penicillin/streptomycin (Gibco), as well as 50 µg/mL Geneticin (G418, Sigma-Aldrich) to limit fibroblast overgrowth.…”
Section: Human Pancreatic Cellsmentioning
confidence: 99%
“… 43 , 44 , 45 , 46 More important, recent findings suggest that CVB4 infection of human primary pancreatic ductal cell cultures impairs differentiation into insulin-producing cells. 47 We therefore checked for the presence of polyhormonal cells (secreting glucagon and insulin), a phenomenon partly mediated by the loss of PDX1. 43 Significantly, confocal images of Uri1 flox/flox ; Pdx1-cre pancreatic islets showed increased polyhormonal cells ( Figures 3 K and 3L).…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated the persistence of CV-B4 in human pancreatic islets [ 28 ] in human primary ductal pancreatic cells [ 38 ] and in a human β cell line (1.1 B4) produced by fusion of human pancreatic β cells with a human pancreatic duct cell line (Panc-1) [ 29 ]. This latter model of β cell does not produce insulin; therefore, it is not suitable for investigating the impact of virus persistence on the production of this hormone.…”
Section: Discussionmentioning
confidence: 99%
“…In this model of acute infection, a decrease in insulin secretion was demonstrated [ 39 ]. Recently, it was shown that insulin mRNA expression and C-peptide levels were inhibited by persistent CV-B4 E2 infection in human primary pancreatic ductal cells differentiated into ICA in vitro [ 38 ]. Furthermore, Yin et al reported that persistent infection of human pancreatic islets with the strain CV-B4 VD2921 did not affect the proinsulin and insulin content of β cells [ 40 ].…”
Section: Discussionmentioning
confidence: 99%